Nonirritating concentrations for skin testing in immediate antibiotic allergy - Florin-Dan Popescu; Maria Caraghiulea; Carmen Saviana Ganea; Mariana Preda; Ana Maria Alexandra Stanescu (Amaltea Medical Publishing House, 2022)
Accurate identification of a culprit drug involved in an immediate hypersensitivity adverse reaction has critical consequences on antibiotic stewardship and patient quality of life, therefore simple reliable diagnostic skin tests are of great importance. Succinct information on the use of positive and negative controls and nonirritating concentrations of antibiotics, according to recent international guidelines, used for skin prick tests and intradermal tests for the allergy workup is required to avoid false negative or false positive results. The method used, the appropriate drug concentrations, and the criteria for positive skin testing influence the specificity and sensitivity of allergy skin tests.